2014
DOI: 10.1111/jphp.12134
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent internalisation of folate-decorated nanoparticles via the pathways of clathrin and caveolae-mediated endocytosis in ARPE-19 cells

Abstract: Increased uptake rate of folate-decorated NPs into RPE cells is observed with increasing degree of folate modification. These NPs utilize both clathrin- and caveolae-mediated receptor-mediated endocytosis pathways to enter RPE cells upon size variation. The 50 nm NPs are internalized the fastest, with clathrin-mediated endocytosis as the preferred route. Uptake of 250 nm particles is the slowest and is dominated by caveolae-mediated endocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 24 publications
3
97
0
2
Order By: Relevance
“…It has been reported that smaller nanoparticles undergo endocytic uptake by cells more easily and rapidly than larger one. 41,42) These previous observations are in accordance with our present results.…”
Section: Discussionsupporting
confidence: 83%
“…It has been reported that smaller nanoparticles undergo endocytic uptake by cells more easily and rapidly than larger one. 41,42) These previous observations are in accordance with our present results.…”
Section: Discussionsupporting
confidence: 83%
“…However, 250 nm nanoparticles, were only internalized via caveolae-mediated pathway [35], despite some articles have described an upper limit size of ~150 nm for passage through caveolae vesicles [36]. …”
Section: Resultsmentioning
confidence: 99%
“…It seems that the internalization of folate-decorated NPs is a size-dependent phenomena medicated via either clathrin-coated pits or caveolae-mediated endocytosis [57]. For example, NPs with size range about 50 nm appear to internalize quickly selectively through the clathrin-mediated endocytosis, while the internalization of NPs with size range at ~250 nm seems to be a slow process via the caveolae-mediated endocytosis as a dominant path.…”
Section: Discussionmentioning
confidence: 99%